An enhanced static compensator with dc-link voltage shaping method - Jeon, Young-Tae (2020)
This paper proposes a dc-link voltage shaping method for a cascaded H-bridge (CHB) static synchronous compensator (StatCom). A recently proposed low capacitance-StatCom system, which intentionally operates with large voltage ripples on the dc-link capacitors, offers the advantage of superior harmonic performance. However, the capacitor voltage ripples decrease when operating at below-rated reactive current, which removes the aforementioned harmonic performance benefit of this system. In addition, such harmonic performance benefit is only achieved in capacitive operation mode. In order to expand the operating region where advantageous voltage ripples are present, a new voltage shaping method is proposed. The proposed method uses a CHB multilevel converter coupled with simple dc-dc converters to shape voltage ripples on the dc-link capacitor regardless of its operating point. This is achieved by controlling the average current of the dc-dc converter using model predictive control (MPC). The concept is best applied to an enhanced StatCom, or E-StatCom, application in which the StatCom is integrated with either a renewable energy source or energy storage system. The operational principle of the proposed approach is validated via simulation and experimental results on a five-level single-phase CHB StatCom.